Integrasi Kurikulum Turos dan Kurikulum Nasional dalam Membentuk Karakter Santri Berbasis Trilogi dan Panca Kesadaran Santri - Ahmad Zubaidi; Virna Budiarti (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The integration of the Turos Curriculum and the National Curriculum at Ma’had Aly Nurul Jadid represents a strategic effort to address the demands of contemporary Islamic education, which emphasizes a balance between mastery of classical Islamic knowledge and modern academic competencies. This study aims to analyze the process and outcomes of integrating these two curricula in shaping students’ character based on the values of Trilogi Santri and Panca Kesadaran Santri. The research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation involving administrators, lecturers, and students as research subjects. The findings indicate that curriculum integration is implemented through the synchronization of Islamic and general subjects, habituation of religious practices, and the strengthening of students’ social and organizational activities. The novelty of this study lies in positioning Trilogi Santri and Panca Kesadaran Santri not only as moral values but also as epistemological and pedagogical foundations. Thus, curriculum integration is understood as a process of value internalization and character formation, producing students who are religious, possess strong integrity, demonstrate intellectual competence, and are adaptive to social dynamics and contemporary developments